Reading Comprehension Learning Model in English Text Using Scanning and Skimming Methods in Physical Education, Health and Recreation Study Program Stok Bina Guna - Syahrul Efendi Lubis; Khairul Usman (Jurnal Mantik, 2021)
The author tried to create a learning model reading comprehension in English text by using scanning methods and skimming. The purpose of this study was to determine whether there was an effect of the reading comprehension learning model in English texts using scanning and skimming methods in the STOK Bina Guna PJKR Study Program. The benefits of this research are to determine the effect of the learning model and improve students' ability in reading comprehension, especially with English texts, so that students can apply both methods when trying to get information from English texts quickly. This research is classroom action research. This research was conducted in a cyclical assessment process through two cycles consisting of four stages, namely planning, action, observation, and reflection. Observations was made by observers in this study concluded that student behavior during reading comprehension learning with scanning and skimming techniques in cycle II could be said to be good. However, there are some students who still behave badly during the lesson. From the results of observations, there were 34 students who behaved well during the lesson, while 3 students who did not behaved well. Of the three students, as many as 2 students often turn off the camera during the test. Meanwhile, there are no more students who have bad habits in reading. Based on the results of these observations, student behavior during reading comprehension learning was good and there was an improvement.